2007
DOI: 10.1086/521421
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Simulation of Competition between Hydrogenation and Photolysis in the Chemical Evolution of H2O‐CO Ice Mixtures

Abstract: Hydrogenation and photolysis of H 2 O-CO binary ice mixtures at 10-50 K have been revisited in order to quantitatively evaluate their relative importance in the chemical evolution of interstellar dust icy mantles. The dominant product of photolysis was CO 2 , with lower yields of formaldehyde, methanol, and formic acid, while only formaldehyde and methanol were obtained by hydrogenation reactions. Hydrogenation has higher formation efficiencies and yields of formaldehyde and methanol than photolysis. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
115
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(128 citation statements)
references
References 45 publications
12
115
1
Order By: Relevance
“…In dense molecular clouds the fractional abundance of CO is on the order of 10 −4 with respect to H 2 (Frerking et al 1982). Experimental results revealed that CH 3 OH can be produced efficiently by successive hydrogenation of CO on grain surfaces at temperatures that are typical in molecular clouds (Watanabe et al 2007;Fuchs et al 2009), and the amount of CH 3 OH obtained is at least on the order of 10 −1 with respect to CO. Other authors suggest that this amount could be higher (Fuchs et al 2009). Thus if we assume high CO depletion we can say that the fractional abundance of solid CH 3 OH is on the order of 10 −5 with respect to H 2 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In dense molecular clouds the fractional abundance of CO is on the order of 10 −4 with respect to H 2 (Frerking et al 1982). Experimental results revealed that CH 3 OH can be produced efficiently by successive hydrogenation of CO on grain surfaces at temperatures that are typical in molecular clouds (Watanabe et al 2007;Fuchs et al 2009), and the amount of CH 3 OH obtained is at least on the order of 10 −1 with respect to CO. Other authors suggest that this amount could be higher (Fuchs et al 2009). Thus if we assume high CO depletion we can say that the fractional abundance of solid CH 3 OH is on the order of 10 −5 with respect to H 2 .…”
Section: Discussionmentioning
confidence: 97%
“…Both CO and CH 3 OH are found to be abundant within the grain mantles. Recently, it was experimentally shown that CH 3 OH can be produced efficiently by successive hydrogenation of CO (Watanabe et al 2007;Fuchs et al 2009). As a consequence, these two components are supposed to reside well mixed in the icy mantles.…”
Section: Introductionmentioning
confidence: 99%
“…However, the formation mechanism of the CO 2 ice still remains unclear, and it is one of the key topics in astrochemistry. Laboratory experiments indicate that the CO 2 ice is efficiently produced by the UV photon irradiation to H 2 O-CO ice mixtures (e.g., Gerakines et al 1996;Watanabe et al 2007). It is reported by several authors that the LMC has an order-of-magnitude stronger UV radiation field than our Galaxy owing to its active star formation and its metal-poor environment (Israel et al 1986;Lee et al 2007).…”
Section: Large Co 2 /H 2 O Ice Ratio In the Lmcmentioning
confidence: 98%
“…However, in the previous section, we mentioned that the UV irradiation can help form CO 2 ice. Several authors have demonstrated by simple calculation that the interstellar radiation field can penetrate the site where the CO 2 ice forms (e.g., Whittet et al 1998;Watanabe et al 2007). We therefore suggest that the external (interstellar) UV radiation field may play an important role in CO 2 ice formation.…”
Section: Correlation Of Ice Abundance With Yso Propertiesmentioning
confidence: 99%
“…For the last two decades, microwave discharge hydrogen-flow lamps (MDHLs;Warneck 1962;Davis & Braun 1968) have been widely used as vacuum-ultraviolet (VUV) light sources in laboratory experiments to simulate interstellar radiation fields in astrochemical studies (Westley et al 1995;Gerakines et al 1996;Baratta et al 2002;Muñoz Caro et al 2002, 2010Cottin et al 2003;Leto & Baratta 2003;Loeffler et al 2005;Watanabe et al 2007;Öberg et al 2007;Islam et al 2014;Cook et al 2014;Henderson & Gudipati 2015). These experiments aim to simulate and ultimately unravel the complex photoprocesses (photodesorption, photodissociation, and photochemistry) taking place in interstellar ice analogues.…”
Section: Introductionmentioning
confidence: 99%